MENYOAL KONSEP MURÂBAHAH DAN BAY’ BI TSAMAN ‘AJIL DALAM PERBANKAN ISLÂM - Holis Rahbini Holis Rahbini (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2011)
Abstract: In Indonesia, Syarî’ah banking is not genuinely born from the “womb” of Islam. However, it is the result of the interference of western system and converted from conventional bank. This article is to describe the terms of Murabahah and bay’ bi tsaman ’ajil conceptually and substantially. In fiqh, the term of murabahah and bay’ bi tsaman ‘ajil are derived from the word bay’ (purchase and sale), yet the term seems ambiguous from the perspective of product of banking. Consequently, it turns up a doubtful concept if it matches conceptual and substantial term. Theoretical concept of murabahah and bay’ bi tsaman ‘ajil is not as simple as the practical one. The practical apllication of murabahah and bay’ bi tsaman ‘ajil is in a dilemma: firstly, in Islamic banking murabahah and bay’ bi tsaman ‘ajil function as financial facilitator not a finacial vendor. This is alike to conventional banking. Secondly, in the transaction of murabahah and bay’ bi tsaman ‘ajil, the credit system appears, unfortunately, it refers to the rate of interest. Key Words: Murâbahah, bay’ bi tsanam ’ajil, bunga, dan bank konvensional